Specimen shape and size effects on the concrete compressive strength under static and dynamic tests - Li, Mei; Hao, Hong; Shi, Y.; Hao, Yifei (Elsevier BV, 2018)
© 2017 Elsevier Ltd Cylinder and cube are two common specimen shapes used in compressive tests to determine concrete strength. Many studies have proposed empirical relations to convert the static strengths of concrete obtained from specimens of these two shapes. There is, however, no study of the relations to convert the dynamic strengths of cylindrical and cubic concrete specimens obtained from impact tests. In this study, cubic and cylindrical concrete specimens of different sizes were prepared and tested under static and impact loads to investigate the shape and size effects on the concrete compressive strength under different loading rates. To investigate the influences of strength on these relations, concrete specimens of two characteristic strengths were made and tested. Cubes of dimension 50 mm and cylinders of diameter 50 mm with various length-to-diameter ratios were cast and tested. Empirical relations that correlate the static and dynamic compressive strengths of concrete obtained from specimens of different shapes and sizes were proposed. The crack patterns of different samples in both static and dynamic tests and their influences on the obtained compressive strengths were also analyzed. The results clearly demonstrate the influences of the specimen shape and size on the obtained compressive strength under static and dynamic tests.